The Determinants of Millennial Farmers' Income: The Role of Capital, Education, and Technology - Budianto, Azis Tri; Widodo, Ageng; Dumadi, Dumadi; febrayanto, catur raharjo; Susiyanti, Fitri; Nugraha, Muhammad Siwi; Yulianto, Mohammad Agus; Hirbasari, Ira Amanda (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 18 No 3 (2024), 2025)
This study investigates the factors influencing the income of millennial farmers in Brebes Regency, Indonesia, a region known for its agricultural sector. The objectives are to determine the profile of millennial farmers and analyze the relationship between education level, knowledge of pests and fertilizers, mechanization, access to capital, and infrastructure, with the income level of young farmers. This research employs a mixed-methods approach, combining quantitative and qualitative analyses. Quantitative analysis utilizes correlation and simple linear regression tests on data collected from a representative sample of millennial farmers in the region. Qualitative analysis is based on in-depth interviews with staff from the Brebes Regency Agriculture and Food Security Agency and millennial farmers themselves. Results indicate that education level, knowledge of pests and fertilizers, and the use of agricultural mechanization among Brebes millennial farmers are already at adequate levels. However, access to capital, particularly the size of cultivated land, is a more significant factor influencing farming activities and income among millennial farmers in Brebes Regency. Therefore, policy planning aimed at expanding the agricultural land available to young farmers is crucial for significantly improving the economic well-being of millennial farmers in Brebes Regency.